Experimental studies of extractive distillation in the presence of an ionic liquid - V. I. Zhuchkov; P. G. Rumyantsev; S. A. Reshetov; T. V. Chelyuskina; A. K. Frolkova (Тонкие химические технологии)
In a full-sized experiment the possibility of different azeotropic mixtures separation with the use of 1-butyl-3-methylimidazolium chloride an ionic liquid, [bmim][Cl] as an entrainer was proven.